ZOOARCHAEOLOGICAL AND ISOTOPIC INSIGHTS INTO LOCALLY VARIABLE SUBSISTENCE PATTERNS: A Case Study from Late Holocene Southern Haida Gwaii, British Columbia. - ORCHARD, TREVOR J.; SZPAK, PAUL (BC Studies)
A case study is provided on the regional differences in subsistence economies in southern Haida Gwaii, British Columbia (B.C.) during the late Holocene period, referencing isotope research and zooarchaeology. An overview of the archaeological assemblages in Haida Gwaii is provided. The role that fishes played in the subsistence economies in Haida Gwaii is discussed.